Expression profiles of NOD1 and NOD2 and pathological changes in gills during Flavobacterium columnare infection in yellow catfish, Tachysurus fulvidraco - Ran Chen; Zechao Shi; Qianxi Han; Qin Wang; Bingchao Wang; Mengge Guo; Wei Ji; Li Shen (Journal of Fish Biology, 2025)
NOD‐like receptors are significant contributors to the immune response of fish against different types of pathogen invasion. NOD1 and NOD2 genes of yellow catfish ( Tachysurus fulvidraco ) were identified and characterized in this study. Yellow catfish NOD1 and NOD2 have open reading frames (ORFs) of 2841 and 2949 bp, encoding 946 and 982 amino acids, respectively. Both NOD1 and NOD2 are intracellular proteins lacking transmembrane regions and signal peptides. Sequence homology analysis revealed that the protein sequences of NOD1 and NOD2 of yellow catfish are highly similar to those of channel catfish. Both NOD1 and NOD2 showed high expression in the head kidney, and spleen. Following challenge with Flavobacterium columnare , NOD1 expression obviously increased in the liver, spleen, midgut, and hindgut, whereas NOD2 clearly increased in head kidney, and gut. Microscopic observation of gill tissues revealed evident epithelial hyperplasia in the secondary gill filaments at 3 and 6 hpi, with a notable decrease in the aspect ratio in comparison with the control group, followed by a return to baseline levels. These findings indicate a potential involvement of NOD1 and NOD2 genes in defense against F. columnare invasion. The findings of this study contribute valuable insights into NOD1 and NOD2 's functions in the innate immune response of yellow catfish and other fish species to bacterial infection.